Intestinal dysbiosis and innate immune responses in axial spondyloarthritis. Issue 4 (July 2016) - Ciccia, Francesco; Ferrante, Angelo; Triolo, Giovanni
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose of review: Inflammatory innate and adaptive immune cell responses to commensal bacteria underlie the pathogenesis of human chronic inflammatory diseases. Intestinal dysbiosis has been described in patients with spondyloarthritis (SpA) and seems to be correlated with histologic and immunologic alterations. Purpose of this review is to discuss the relationship occurring between intestinal dysbiosis and innate immune responses in patients with axial SpA. Recent findings: Intestinal dysbiosis and differential activation of intestinal immune responses in patients with SpA have been demonstrated. Furthermore, innate cells that appear to be involved in the pathogenesis of SpA may control intestinal homeostasis through induction of apoptotic cell death and deletion of activated commensal bacteria-specific T cells. Summary: Although the evidence shows that dysbiosis occurs in SpA, it is not clear the role of dysbiosis in regulating innate immune responses in SpA. Relationships between cause and effect remain to be answered. Video abstract: http://links.lww.com/COR/A34 .